PROMOTING COLLABORATION AS CHARACTER EDUCATION VALUE THROUGH DIGITAL STORYTELLING IN ENGLISH TEACHING FOR YOUNG LEARNERS - Putra, Gede Susila Darma; Luh Putu Artini; Luh Indrayani (Yavana Bhasha : Journal of English Language Education, 2026)
Collaboration is an essential character education value that supports meaningful learning in English as a Foreign Language classrooms for young learners, yet it is often insufficiently integrated into instructional practices. This study examines how digital storytelling is used to promote collaboration as a character education value in English teaching for young learners. A systematic literature review was conducted by analyzing eighteen relevant studies published between 2020 and 2025. The study followed a structured review process to identify, screen, and synthesize eligible articles, which were then analyzed thematically. The findings reveal that digital storytelling is commonly implemented as a collaborative and project-based learning activity that integrates language learning with social interaction through multimodal resources. Collaboration is fostered through small-group work, role distribution, joint planning, peer feedback, and shared problem-solving throughout the storytelling process. Digital storytelling activities are generally designed using structured instructional stages, with teachers acting as facilitators and learners functioning as active participants and co-creators. The study concludes that digital storytelling effectively supports the development of collaboration as a character education value while also enhancing young learners’ engagement and English language learning. These findings highlight the potential of digital storytelling as an instructional approach that integrates language development and character education in English as a Foreign Language classrooms for young learners.